First histological description of pulmonary and vascular abnormalities of pulmonary hypertension associated with KDR pathogenic variant. Issue 5 (3rd November 2022) - Riou, Marianne; Canuet, Matthieu; Ghigna, Maria-Rosa; Eyries, Mélanie; Chenard, Marie Pierrette; Porzio, Michele; Olland, Anne; Humbert, Marc; Kessler, Romain; Montani, David
Loss of function (LoF) pathogenic variants in the kinase insert domain receptor ( KDR ) gene have recently been associated with heritable pulmonary arterial hypertension (PAH) [1–3]. The KDR gene encodes the second tyrosine kinase receptor, vascular endothelial growth factor receptor 2 (VEGFR-2) for VEGF-A, that transduces the signal of the vascular endothelial growth factor (VEGF) pathway that is highly expressed in the lungs and necessary for the development of lung vasculature during embryogenesis and for the maintenance of the pulmonary vessels and alveolar structures in adults [4, 5]. Thus, a decrease of VEGF signalling induced by KDR LoF variants could lead to PAH, as was described in vitro and in animal models [6, 7]. This study confirms that KDR loss of function variants are associated with interstitial and pulmonary vascular remodelling, alveoli alterations, mild emphysema and possible vascular systemic involvement https://bit.ly/3SmTrpW